Incentives for smoking cessation - Notley, C; Gentry, S; Livingstone-Banks, J; Bauld, L; Perera, R; Hartmann-Boyce, J (Cochrane Collaboration, 2019)
Background Financial incentives, monetary or vouchers, are widely used in an attempt to precipitate, reinforce and sustain behaviour change, including smoking cessation. They have been used in workplaces, in clinics and hospitals, and within community programmes.